Optimalisasi Peran Mediator dalam Penyelesaian Perselisihan Hubungan Industrial di Dinas Tenaga Kerja Provinsi Sumatera Utara - Rudi Alfahri Rangkuti; Ida Nadhirah (Mahesa Research Center, 2023)
The purpose of this study was to determine the optimization of the role of the mediator through mediation and the obstacles carried out at the Manpower Office of North Sumatra Province in resolving industrial relations disputes through a dispute resolution theory approach. This research is normative juridical research through the approach of statutory regulations and legal principles, the nature of the research is descriptive-analytical, namely describing problems that occur next are discussed and analyzed, data sources obtained from secondary data through government publications/websites, data collection tools are carried out through documents or, and the data analysis used is qualitative analysis. This study concludes that the role of the mediator in resolving industrial relations disputes is not optimal due to the mediator's lack of knowledge in the field of employment, failure to convey SOPs in mediation, resulting in unavoidable commotions and the mediation process is terminated. Mediators often blame one of the parties in the mediation process and tend to side with the workers, in the end the employer often decides to settle the dispute through the courts. The attitude of the mediator seems authoritarian and judges the parties, resulting in the suboptimal role of the mediator in providing solutions to dispute resolution. The obstacle to optimizing the role of the mediator is the process of asking for information which does not simultaneously raise the suspicions of the parties towards the mediator. Efforts to increase the expertise of mediators to ensure the role of mediators through the submission of SOPs.